Exploring the dynamic reading of environment towards a multidimensional legibility - Putri Mahsa Gantari; Ferro Yudistira (Department of Architecture Faculty of Engineering Universitas Indonesia, 2023)
This study investigates the understanding of legibility, defined as the coherency of built environment features. Legibility enables production of mental image that helps individuals with their spatial navigation. The current discussion positions legibility as an objective aspect in the process of making sense of the environment. The study argues that such a process has dynamics that reflect individuals' subjectivity, therefore further study is important to reconcile the objective and subjective reading of legibility. This research qualitatively investigates legibility using a case study of an indoor environment of a shopping mall in East Jakarta. The analysis was conducted based on the objective and subjective aspects which construct individuals' cognitive map. The objective-based analysis examines the complex topological interconnection and good form principles, as well as the landmark potential based on visual, semantic, and structural saliency. Meanwhile, the subjective-based analysis focuses on examining the spatial knowledge represented through the cognitive map produced based on the respondents' experiences. The analysis shows the multidimensional nature of legibility derived from a dynamic process during the encounter between individuals and the environment. The reconciliation of the objective and subjective aspects of legibility integrates two- and three-dimensional spatial knowledge. The multidimensions of legibility demonstrate ways of revealing the complexity of the built environment, triggering various design approaches.